Research on Flood Disaster Simulation of Hongqi River Basin Based on HEC-RAS. Issue 2 (May 2021) - Sun, Mengmeng; Quan, Hechun; Lin, Zhehao
Abstract: At present, flood disasters are one of the main natural disasters in the world, and the research on flood disasters in current geography is also a research hotspot in recent years. Floods pose a serious threat to people's lives and properties such as farmland and urban areas. Research on flood simulation can help reduce such losses to a certain extent. This paper takes the Hongqi River Basin in the upper reaches of the Tumen River as the research area, applies the Terrain Digital Elevation Model (DEM), uses the HEC-RAS model, and combines the HEC-GeoRAS module under the ArcGIS platform to build on the Tumen River as the terrain is more complicated. The hydrodynamic simulation of flood water flow when flood disaster occurs in the river basin, the rough visual analysis of the flood situation in the Hongqi River Basin, and the comparison and analysis with the measured data, will be used for future flood control early warning, disaster assessment, and Project site selection and other work provide reference data. The simulation analysis shows that HEC-RAS has a good simulation effect in this area and can provide decision support for flood prevention and control.